Value of Insurance : a Corporate Finance Perspective - Wieczorek-Kosmala, Monika (Wartość ubezpieczenia z perspektywy finansów przedsiębiorstwa, 2010)
The value of insurance for the company can be perceived from different perspectives. The paper identifies insurance value drivers through the analysis of core benefits related to applying insurance as a tool of risk management. Particularly, two aspects are analysed: the insurance risk transfer mechanism and the process of practical application of insurance in a company. Each of the identified insurance value drivers is discussed in terms of its impact on value creation process perceived through the economic value added account. The discussion is concluded with the model of net of connections between each of the identified insurance value drivers and economic value added account components. The model includes a character and a course of actions between its elements.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 125, s. 152-169
Keywords: insurance; value; economic value added; JEL codes: G22, G32